2019
DOI: 10.1097/sla.0000000000002803
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability and Programmed Cell Death-Ligand 1 Expression in Stage II/III Gastric Cancer

Abstract: MSI status and PD-L1 expression are clinically actionable biomarkers for stratifying patients and predicting benefit from adjuvant chemotherapy after D2 gastrectomy for stage II/III gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
182
3
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(217 citation statements)
references
References 46 publications
13
182
3
3
Order By: Relevance
“…An important result observed in the present study was the absence of benefit from POP/AD treatment to MSI subgroup defined by IHC, similar to the findings previously described in phase III trials . Furthermore, we found a higher proportion of MSI compared with MAGIC and CLASSIC trials (17.4% vs 8.2% and 6.8% respectively), in addition to 10% EBV positive tumors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An important result observed in the present study was the absence of benefit from POP/AD treatment to MSI subgroup defined by IHC, similar to the findings previously described in phase III trials . Furthermore, we found a higher proportion of MSI compared with MAGIC and CLASSIC trials (17.4% vs 8.2% and 6.8% respectively), in addition to 10% EBV positive tumors.…”
Section: Discussionsupporting
confidence: 91%
“…In MAGIC and CLASSIC trials MSI GC had a better prognosis irrespective of treatment received, and it is postulated that the production of new immunogenic epitopes due to the defective repair system activates peritumoral lymphocyte infiltration and systemic T cell activation, which could be downregulated by cytotoxic chemotherapy …”
Section: Discussionmentioning
confidence: 99%
“…MSI status was not a clear predictive biomarker of the effect of adding radiotherapy to adjuvant chemotherapy. Noteworthy, based on the CLASSIC study results [13] and the well-known greater benefit from chemotherapy in Asian GC patients, adjuvant chemotherapy may not be detrimental, but neither beneficial, in MSI-high Asian GC patients, and the same is true for adjuvant radiation treatment based on the present study results. Future prospective trials should investigate the omission of chemotherapy in patients with a lower clinico-pathological risk and MSI-high GC.…”
Section: Discussionsupporting
confidence: 63%
“…Regarding adjuvant treatment, Choi reported in a secondary analysis of the CLASSIC trial (comparing surgery and adjuvant chemotherapy with surgery alone) a better relapse‐free survival of MSI‐H cancer patients after surgery alone in comparison to non‐MSI‐H cancer patients. No benefit of adjuvant chemotherapy was observed among the MSI‐H cancer patients . In a big retrospective cohort study including 1,276 patients, Kim et al showed that patients with stage II/III MSI‐H tumors had no benefit of adjuvant chemotherapy; in addition, even a detrimental effect of adjuvant chemotherapy was observed in subgroups with stage III disease, undifferentiated histology and diffuse type tumors …”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer the prognostic implications are less clear. A better outcome for patients with MSI‐H tumors than with MSS tumors has been reported in a recent meta‐analysis by Polom and colleagues, whereas the benefit of perioperative or adjuvant chemotherapy seems to be unclear according to exploratory analyses of recent phase III trials …”
Section: Introductionmentioning
confidence: 95%